Pengaruh Kecemasan Matematika dan Prokrastinasi Akademik Terhadap Hasil Belajar Siswa - Inas Nada Nailussulha; Nurul Hikmah; Dwi Novitasari (Mandalika Mathematics and Educations Journal, 2026)
This study aims to determine the effect of mathematics anxiety and academic procrastination on the learning outcomes of eighth-grade students at a public junior high school in West Lombok regarding exponents during the 2025/2026 academic year. This research employed a quantitative approach using the ex-post facto method. The sample consisted of 55 students selected through a simple random sampling technique. The research instruments included a mathematics anxiety questionnaire, an academic procrastination questionnaire, and a mathematics achievement test. Data were analyzed using simple and multiple linear regression with the assistance of SPSS. The results showed that mathematics anxiety had a negative and significant effect on students’ learning outcomes, with a significance value of 0.006 < 0.05 and a regression coefficient of –1.008. Academic procrastination also had a negative and significant effect, with a significance value of 0.046 < 0.05 and a regression coefficient of –1.314. Simultaneously, both variables significantly affected learning outcomes, as indicated by an F-value of 16.239 and a significance value of 0.000 < 0.05. The coefficient of determination (R2) was 0.384, indicating that 38.4% of the variation in learning outcomes was explained by mathematics anxiety and academic procrastination, while the remaining 61.6% was influenced by other factors beyond this study. These findings emphasize the important role of affective and behavioral factors in supporting students’ mathematics achievement.